2016
DOI: 10.2147/copd.s111724
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of comorbidities according to predominant phenotype and severity of chronic obstructive pulmonary disease

Abstract: BackgroundIn addition to lung involvement, several other diseases and syndromes coexist in patients with chronic obstructive pulmonary disease (COPD). Our purpose was to investigate the prevalence of idiopathic arterial hypertension (IAH), ischemic heart disease, heart failure, peripheral vascular disease (PVD), diabetes, osteoporosis, and anxious depressive syndrome in a clinical setting of COPD outpatients whose phenotypes (predominant airway disease and predominant emphysema) and severity (mild and severe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 39 publications
7
22
1
5
Order By: Relevance
“…COPD was associated with other diseases in up to 80% of the patients in our series, the most common comorbidity being arterial hypertension; these data coincide with the findings of most previously published studies 40,41. When comorbidities were analyzed according to the use of tobacco, it was found that patients with osteoporosis were more likely to be active smokers.…”
Section: Discussionsupporting
confidence: 91%
“…COPD was associated with other diseases in up to 80% of the patients in our series, the most common comorbidity being arterial hypertension; these data coincide with the findings of most previously published studies 40,41. When comorbidities were analyzed according to the use of tobacco, it was found that patients with osteoporosis were more likely to be active smokers.…”
Section: Discussionsupporting
confidence: 91%
“…Recent work by Camiciottoli et al 35 described different panels of comorbidities among patients with predominant chronic bronchitis phenotype versus patients with emphysema. It is possible frailty may be more common in certain phenotypes and the mechanisms driving the presence of frailty within a diagnosis may vary.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variable in the multivariate analysis was the diagnosis of the comorbidity. We selected as independent (explanatory) variables those variables with a previously reported association in the medical literature (age [17] , gender [5] , severity of COPD [5, Golpe et al , and clinical phenotype [6] ) or with biological plausibility of an association (frequent COPD exacerbations and the type of smoke exposure, which was the basis for the working hypothesis). Age was coded in 1-year increments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study provides the opportunity to test the interactions between sex and other variables in B-COPD. Another strength is that, unlike some studies carried out using administrative databases, the diagnosis of COPD was objectively confirmed with lung function testing, and we were able to include explaining variables, such as severity of the ventilatory obstruction and the COPD phenotype, that in previous studies have been found to be associated with comorbidities [5,6] .…”
Section: Discussionmentioning
confidence: 99%